Mengaktualisasikan Amanat Agung Matius 28:19-20 dalam Konteks Era Digital - Handreas Hartono (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2018)
Great comission is a mandate that Jesus gave to His disciples before He ascent to the heaven. This mandate has often been implemented to be a mere act of evangelization, how to make people believe in Jesus for their salvation sake. The world where church lived today has changed by applying advanced technology in all human life aspect, for generally called the era of digitalization. There were some different challenges and needs of todays church with the early church who received that mandate in the first century. Thus this is an article aimed to explain how to actualize a great commission according to Matthew 28:19-20 in a different world today, which called the era of digital. This article used a qualitative method with an analytical approach to the text of Matthew 28:19-20, and a descriptive of the era of digital today as a context of actualizing that great commission. As a conclusion, the church ought to apply the advanced technology with digitization to reach out people in the world where unreached yet.AbstrakAmanat agung merupakan sebuah mandat yang Yesus berikan kepada murid-murid-Nya sebelum Ia naik ke surga. Perintah ini sering diimplementasikan dengan sekadar tindakan penginjilan, bagaimana membuat orang menjadi percaya Yesus demi keselamatannya. Dunia di mana gereja hidup sekarang telah berubah oleh karena kemajuan teknolgi yang merambah seluruh aspek hidup manusia, yang biasa disebut dengan era digitalisasi. Oleh sebab itu ada perbedaan tantangan dan kebutuhan yang dialami oleh gereja sekarang dengan gereja mula-mula di abad pertama. Maka dengan demikian, artikel ini bertujuan untuk menjelaskan bagaimana mengaktualisasikan amanat agung dalam Matius 28:19-20 dalam konteks dunia di era digital. Artikel ini merupakan penelitian kualitatif dengan pendekatan analisis atas teks Matius 28:19-20, dan deskriptif atas konsep dunia di era digital sebagai konteks untuk mengaktualisasikan amanat agung tersebut. Sebagai kesimpulan, gereja harus mengaplikasikan kemajuan teknologi digitalnya untuk menjangkau orang-orang yang selama ini belum terjangkau.